2017
DOI: 10.1177/1464884917692820
|View full text |Cite
|
Sign up to set email alerts
|

Changed priorities ahead: Journalists’ shifting role perceptions when covering public health crises

Abstract: Journalistic role perceptions have been extensively studied in general contexts, but little is known as to how roles – or role prioritization – may shift across contexts, and professional characteristics. The aim of this study was gaining an understanding of journalists’ changing role perceptions in health crisis coverage, and moreover to examine potential differences between general and specialist reporters. We conducted 22 in-depth interviews with reporters with experience in health crisis reporting in Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 47 publications
1
40
2
1
Order By: Relevance
“…The journalistic professional detachment was side-stepped when the journalists became instructors. This finding is contrary to previously reported journalist roles in disaster settings, where journalists tried to maintain independence despite disseminating public health messages [10][11][12][13][14]. Journalistic independence is a construct that is ascribed different importance in different parts of the world [38].…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…The journalistic professional detachment was side-stepped when the journalists became instructors. This finding is contrary to previously reported journalist roles in disaster settings, where journalists tried to maintain independence despite disseminating public health messages [10][11][12][13][14]. Journalistic independence is a construct that is ascribed different importance in different parts of the world [38].…”
Section: Discussioncontrasting
confidence: 74%
“…In the initial phase of a disaster, there can be speculation in the media, followed by a phase in which journalists commonly try to contextualize the disaster and aim to take on a longer-term perspective [9]. In each of these phases, journalists have been reported to take on different roles [10][11][12]. For instance, they can be public advocates, shining a light on underrepresented people, a catalyst by drawing attention to budget issues, or a public safety official, giving people warnings and information on risks associated with the disaster [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between journalism and public health has mostly been explained based on journalistic roles and news framing. During the 2009 H1N1, for instance, Klemm et al (2017) found that journalists shifted from ‘watchdogs’ to ‘cooperative’ roles. Holland et al (2014) further argued that the 2009 H1N1 enabled journalists to be reflexive of their roles especially with conflicts of interest among experts and decision makers.…”
Section: Introductionmentioning
confidence: 99%